Pelatihan Penyelenggaraan Jenazah Menurut Hukum Islam: Suatu Kegiatan PKM Yang Bermakna : Studi Di Desa Sialang Panjang Kecamatan Tembilahan Hulu Kabupaten Indragiri Hilir Provinsi Riau - Kafrawi Kafrawi; Muhammad Ilyas; Mulyadi Mulyadi; Abdul Syahid; Fahrina Yustiasari Liriwati (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
Training on handling corpses according to Islamic law is an in-depth activity in a religious and humanitarian context. This article discusses the importance of this training in understanding, respecting and carrying out funeral arrangements in accordance with Islamic teachings. This training provides the basic knowledge, practical skills, and cultural and ethical understanding needed to carry out the task of handling corpses properly. In addition, this article highlights the important benefits of Student Creativity Program (PKM) activities in expanding religious understanding, increasing respect for religious values, and empowering communities to play an active role in funeral services in accordance with Islamic guidelines. Through these efforts, we can create a society that is more aware of their religious practices, respects traditions, and applies Islamic teachings with full respect in the care of corpses.